ANTISIPASI KONFLIK PERAN PADA KELUARGA DAN PEKERJAAN, STUDI PADA MAHASISWA FAKULTAS TEKNIK UNIVERSITAS GADJAH MADA - , NADHIA AYU TIKA ARDIANTI B. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Nowadays, issue of gender to be one issue that is often discussed in a variety of fields. However, research on gender in engineering education is still lacking, especially in Indonesia. Based on that fact, the study will analyze about gender differences that exist in the field of engineering education. This research was conducted with the aim of finding out if the difference in perception between male and female students to role conflicts they will face later. This study will take a sample of college women and men who take education in the Faculty of Engineering. To see the difference in perception between male and female students to role conflict, this study using independent samples t test. The study of 100 respondents showed a difference in perception between male and female students to role conflict anticipation.